Positive Law of Environment and John Ruggie Principles: Between Legal Text and Norms - Iwan Erar Joesoef (Jurnal Manajemen Hutan Tropika, 2022)
The aim of this research is to examine the application of the Guiding Principles for Business and Human Rights, that is Protection, Respect and Recovery in the implementation of the Law on Environmental Protection and Management (Environment Law). In 2015 the government issued the Presidential Regulation Number 75 of 2015 regarding to the National Action Plan for Human Rights 2015-2019 (NAP Human Rights). In 2020 the government is simplifying laws and regulations with the new concept of legal drafting that is the Omnibus Law of which government stated the law of which be familiar as Job Creation Law. One of the simplified clusters is the Environment Law. The findings show that many amended legal norms in the Environment Law are inconsistent with and even contradictory to the NAP Human Rights. Research is carried out normatively by paying attention to legal issues in social media as legal material, as well as reviewing scientific literature related to the topic of issues, laws and regulations, and court decisions. The conclusion from the research is that the Guiding Principles of United Nations for Business and Human Rights bind Judges in enforcing the Environment Law even though these principles are still at the level of the National Action Plan and have not yet entered into the level of legislation.